2021
DOI: 10.3389/fonc.2021.794498
|View full text |Cite
|
Sign up to set email alerts
|

Case Report: Early Association of Vemurafenib to Standard Chemotherapy in Multisystem Langerhans Cell Histiocytosis in a Newborn: Taking a Chance for a Better Outcome?

Abstract: Langerhans cell histiocytosis (LCH) is due to aberrant monoclonal proliferation and accumulation of dendritic cells, ranging from a self-limiting local condition to a rapidly progressive multisystem disease with poor prognosis. Pathogenic cells originate from a myeloid-derived precursor characterized by an activation of the MAPK/ERK signaling pathway in about 70% of cases. In particular, BRAF V600E mutation is usually associated with a more severe clinical course and poor response to chemotherapy. We report on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Although this combination resulted in a significant metabolic response of RDD lesions, leukemia remission was not durable as patient experienced CNS relapse 3 months following combination therapy. Of note, Gaspari et al 8 also reported the safety and efficacity of vemurafenib combined with vinblastine/prednisone in a newborn with multisystem LCH.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…Although this combination resulted in a significant metabolic response of RDD lesions, leukemia remission was not durable as patient experienced CNS relapse 3 months following combination therapy. Of note, Gaspari et al 8 also reported the safety and efficacity of vemurafenib combined with vinblastine/prednisone in a newborn with multisystem LCH.…”
mentioning
confidence: 98%
“…Of note, Gaspari et al . 8 also reported the safety and efficacity of vemurafenib combined with vinblastine/prednisone in a newborn with multisystem LCH. A literature review of children with co-diagnosis of histiocytosis (excluding H group disorders) during ALL treatment identified 30 cases.…”
mentioning
confidence: 99%